Evaluation and implication of noise and vibration levels to the operators and proxy population around selected block molding industries in Ibadan, Nigeria (International Journal of Occupational Safety and Health, 2024)
Introduction: Block-making industries owned by private individuals are cited in cities to utilize the existing market opportunity of supplying concrete blocks to developers. The study aimed to measure noise and vibration levels at selected block-molding industries and assess their health implications.Methods: The study design involves twenty-five block molding industries randomly selected in the Ibadan metropolis. These industries voluntarily agreed to participate in the research, and measurements were done between January and May 2022. The noise and vibration levels were measured using a digital multi-function environmental meter, Model DT-8820, and a vibration meter, Model VM-6360, respectively.Results: An overall mean noise level of 101.81 dB(A), 85.62 dB(A), 76.40 dB(A), 70.21 dB(A), 65.91 dB(A), and 63.61 dB(A) at 0, 10, 20, 30, 40 m, respectively, away from the source to residential buildings were obtained. Results indicate that the noise level at 0 m and 10 m exceeded the occupational noise level standard. The results obtained for the vibration levels on the hand of the operators ranged from 42.2 ms-2  to 59.7 ms-2  and these exceeded the occupational vibration level standard. This may indicate that the operators of the block-moulding machine may be exposed to various adverse health detriments due to high noise and vibration levels at their workplace.Conclusion: The study recommends using safety gadgets such as hearing protection and anti-vibration gloves for workers in these industries. Moreover, environmental education and awareness should be carried out, and residential structures should be situated at least 20 meters from the block industries.